Container terminal operations simulator (CTOS) – Simulating the impact of extreme weather events on port operation - Prem Chhetri; Gaya B. Jayatilleke; Victor O. Gekara; Alex Manzoni; Brian Corbitt (European Journal of Transport and Infrastructure Research, 2016)
This paper develops a methodology to design a Container Terminal Operation Simulation (CTOS), which simulates the vulnerability of port operations to extreme weather events. In CTOS, an agent based model was built for a container terminal at the Port of Sydney to simulate the operations of port operational assets such as cranes, straddle carriers and trucks to observe the individual and collective behaviour under various extreme weather events using a set of Key Performance Indicators (e.g. crane rates, straddle productivity, truck queue length, yard utilisation). The CTOS results show that the crane throughput loss due to six hours of heavy rain and six hours of high speed wind (separately) is 13 per cent within a 24 hour period. While high speed wind and heavy rain have the highest impact on the crane throughput, high speed wind and flooding in the port area leads to a backlog in servicing trucks. Using a single terminal for the purpose of the simulation, as opposed to the entire Sydney Port, is a limitation. However, the CTOS is designed and coded in a manner that permits its modification such that it can be applied to other port contexts. CTOS offers a versatile tool for port authority to enable estimating performance implications of extreme weather-related disruptions to port operations. CTOS provides an effective proof of concept prototype where the system architecture can be reused in developing an open generic port operations model.